(3GdNWHI GdehfbI (B((3NWHI aj Cj GdMQha CONd aj GdcdGe(B)s - (3Ydj Hf CHj WGdH,J (B40 (3g` s
(3ChdgG (B:s
(3bGd Ydj Hf eMeO GdJejej(B: (3MOKfG GdTjN Gdabjg GdYGde GdhGdO Yf eMeO Hf GdSGFH, Yf GdUGOb Yf CHjg Yf LOg Ydj Hf GdMSjf Yf GdMSjf Yf GdEeGe GdgeGe Ydj Hf CHj WGdH Ydjge GdSdGe bGd(B: s
(3BNQgG (B:s
(3hHSW dg hgF hfTQ Ydjg cafg hTO efg Pbfg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B199 - (3U(B199s
(3GfXQgG eY cJGH GdeYQGL ddQGRj (B292 (3EjQGfs
(3hjXf Cf ajgG HJQkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B287 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs